2016
DOI: 10.1016/j.ygyno.2016.03.013
|View full text |Cite
|
Sign up to set email alerts
|

The influence of clinical and genetic factors on patient outcome in small cell carcinoma of the ovary, hypercalcemic type

Abstract: Stage at diagnosis is the most significant prognostic factor in SCCOHT and consolidation with HDC-aSCR may provide the best opportunity for long-term survival. The large fraction of SMARCA4 germline mutations carriers warrants genetic counseling for all patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
121
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 104 publications
(127 citation statements)
references
References 37 publications
4
121
0
2
Order By: Relevance
“…SMARCA4 female mutation carriers have a higher risk of developing small cell carcinoma of the ovary, hypercalcemic type (SCCOHT), which can be regarded as a special type of MRT and was found to be very similar to RTs in clinical, histologic, genomic, and epigenomic characteristics (40)(41)(42). Although these tumors represent a distinct clinical entity, the similarities to MRT have led some to suggest that SCCOHT be considered part of the rhabdoid tumor predisposition syndrome (RTPS) spectrum of tumors (Table 3).…”
Section: Genes Responsible For Rt Predispositionmentioning
confidence: 99%
See 1 more Smart Citation
“…SMARCA4 female mutation carriers have a higher risk of developing small cell carcinoma of the ovary, hypercalcemic type (SCCOHT), which can be regarded as a special type of MRT and was found to be very similar to RTs in clinical, histologic, genomic, and epigenomic characteristics (40)(41)(42). Although these tumors represent a distinct clinical entity, the similarities to MRT have led some to suggest that SCCOHT be considered part of the rhabdoid tumor predisposition syndrome (RTPS) spectrum of tumors (Table 3).…”
Section: Genes Responsible For Rt Predispositionmentioning
confidence: 99%
“…The risk of SCCOHT and the decision to undergo prophylactic surgery will be individualized and informed by the family history, the age of the patient, the patient's reproductive plans, and by emerging data that will help with estimation of risk. SMARCA4-deficient SCCOHT has not been seen in women over age 60 (42), so screening recommendations can be altered in older women.…”
Section: Recommended Surveillance Protocols For Rtsmentioning
confidence: 99%
“…87 92 While the tumour cells in SCCOHT usually have scant cytoplasm resulting in a small cell appearance, some cases contain tumour cells with abundant eosinophilic cytoplasm, often resulting in a large cell appearance, sometimes with a rhabdoid morphology. As discussed below, SCCOHT is caused by mutations in the chromatin remodelling gene SMARCA4 90. These mutations are accompanied by loss of expression of the SMARCA4 (BRG1) protein in 97% of cases, and immunostaining for SMARCA4 has now been established as an extremely useful way to diagnose SCCOHT and distinguishes this entity from its mimics which almost always exhibit retention of nuclear immunoreactivity (figure 2).…”
Section: Small Cell Carcinoma Of the Ovary Of Hypercalcaemic Typementioning
confidence: 99%
“…While RTPS2-associated SMARCA4 mutations are largely loss of function variants, a handful of missense variants have been described 90. These variants have been found to occur across the length of the gene, with no predominant hotspot regions 90.…”
Section: Small Cell Carcinoma Of the Ovary Of Hypercalcaemic Typementioning
confidence: 99%
“…Optimal management of patients is not well defined; in literature several and different treatment strategies and chemotherapy are reported but in few cases due to the rareness of the disease, Harrison et al presented a review of the management of 17 cases in a Gynecological Cancer Intergroup (GCIG) study, with poor results showed [7]. In this context there are no evidence based recommendations nor guide lines (Table 2) [1,3,[8][9][10][11][12][13][14]. We present and discuss a case of SCCOHT in a young patient, as well a review of the literature about ovarian small cell tumors treatment.…”
Section: Introductionmentioning
confidence: 99%